NAB2-STAT6 Gene Fusions to Evaluate Primary/Metastasis of Hemangiopericytoma/Solitary Fibrous Tumors. Issue 5 (2nd June 2021) - Singh, Nirupama; Collingwood, Robin; Eich, Marie-Lisa; Robinson, Alyncia; Varambally, Sooryanarayana; Al Diffalha, Sameer; Harada, Shuko
Abstract: Objectives: Hemangiopericytomas (HPCs) and solitary fibrous tumors (SFTs) were considered two distinct entities, but a common gene fusion, NAB2-STAT6, has been identified in both. Although rare, HPCs and SFTs do metastasize, some many years later after resection. Given the extended disease-free interval, it can be difficult to determine with certainty if an HPC or SFT at a new anatomic location represents a second primary or metastatic disease. Methods: RNA was extracted from formalin-fixed, paraffin-embedded tissue of two patients with multiple SFT/HPC samples. The fusion gene was amplified by reverse transcription polymerase chain reaction (RT-PCR) and a custom-designed Archer FusionPlex panel (94 target genes) and the Illumina NextSeq 550. Results: We identified two patients with multiple resections for HPC/SFT during 26 years at our institution. The first patient had a history of HPC and almost 10 years later she was diagnosed with malignant SFT. The HPC and the SFT shared the same fusion breakpoint. The second patient had multiple lesions in the brain and bone/soft tissue over a 27-year span following a diagnosis of meningeal SFT. Three lesions from this patient shared the same fusion breakpoint. Conclusions: Our study demonstrated the same fusion breakpoints in primary and metastatic SFTs/HPCs at different time points using both RT-PCR and the Archer fusion panel.